PENGARUH INTELLECTUAL CAPITAL PADA KESEHATAN KEUANGAN PERUSAHAAN ASURANSI JIWA DI INDONESIA - Putra, Johny Sumarna; Budiasih, I Gusti Ayu Nyoman (E-Jurnal Akuntansi; Vol 13 No 2 (2015), 2016)
This study aims to determine the effect of intellectual capital on the financial health of insurance companies in Indonesia. The data used are the financial statements and annual reports of the life insurance company officially registered in the Life Insurance Association of Indonesia (AAJI). Company sampled in this study amounted to 13, which has been selected by purposive sampling method. Data was collected through non-participant observation and data analysis techniques used are linear regression berganda.Hasil this study indicate that the variable has no effect on RBC VACA, while VAHU and STVA significant positive effect on RBC. This shows that human capital and structural capital has an important role in the knowledge-based companies such as life insurance companies
Keywords: Value Added Capital Employed (VACA); Value Added Human Capital (VAHU); Structural Capital Value Added (STVA); Risk Based Capital (RBC)